Prosumers’ Needs Satisfied Due to Cooperation with Offerors in the Context of Attitudes toward Such Cooperation - Agnieszka Izabela Baruk (MDPI AG, 2021)
The purpose of this article is to determine final purchasers’ needs satisfied due to cooperation with offerors and the dependencies between these needs and previous behaviors and attitudes toward this cooperation. The results of the world literature analysis indicate a cognitive and research gap regarding the aspects mentioned. In order to reduce the gap, empirical studies were conducted, in which an online questionnaire was used to gather primary data. The research was implemented in the second half of 2020 among 1150 respondents representing Polish adult final purchasers. The data were subjected to quantitative analysis using statistical analysis and statistical testing, including exploratory factor analysis, cluster analysis, Pearson chi-square independence test, V-Cramer contingency coefficient analysis, and Kruskal–Wallis test. The results of the statistical analysis made it possible to verify six research hypotheses. Dependencies were found between needs satisfied due to cooperation with offerors and the following aspects: (1) purchasers’ previous participation in cooperation with offerors, (2) purchasers’ willingness to cooperate with offerors, and (3) the assessment of contemporary purchasers’ readiness to cooperate with offerors. Willingness to cooperate with offerors differentiated all eleven needs satisfied due to cooperation with offerors analyzed in this study. Two other variables differentiated only a few of the needs analyzed. The results obtained from the research have a cognitive and applicability value. They contribute to theory of marketing and market behavior. They can also facilitate establishing and strengthening cooperation between offerors and final purchasers as important partners cooperating in the process of creating a marketing offer. This effect is very important in the case of shaping the cooperation between final purchasers and offerors of different products including energy ones. The originality of the approach proposed is evidenced by the fact it is the first time final purchasers’ needs that can be satisfied due to cooperation with offerors have been analyzed in the context of attitudes and behavior reflecting purchasers’ (1) previous participation in this cooperation, (2) willingness to cooperate with offerors, and (3) the assessment of contemporary final purchasers’ readiness to cooperate with offerors.